Analisis Kesulitan Belajar Siswa di SMA Negeri 2 Bilah Hulu - Sari, Novi Fitriandika; Putri, A Sarinade; Rahma, Indah Fitria; Hsb, Elisa Rohayani; Simamora, Siti Suharni; Wahyuni, Mira (JURNAL PEMBELAJARAN DAN MATEMATIKA SIGMA (JPMS), 2016)
This study aims to determine students' learning difficulties in the matter of the digestive system in humans from the aspect of learning indicators and the factors that cause students' learning difficulties in studying the material of the Digestive System in Humans in class XI IPA SMA Negeri 2 Bilah Huluh. In this study the approach and type of research used is to use a qualitative descriptive approach. The population and sample of this study were taken by means of a total sampling of 89 students. Data collection techniques used were interviews, documentation and questionnaires. Presentation of students' learning difficulties in the aspects of learning indicators, namely (1) structure and function of 61.89% in the medium difficulty category; (2) The digestive process is 80.80% with a high difficulty category; (3) The gear section is 41.29% in the low difficulty category; (4) Enzyme function is 72.00% with high difficulty category; (5) substance in food is 48.50% with medium difficulty category; (6) The function of food is 61.61% in the medium difficulty category; (7) Variation and composition of 61.70% in the medium difficulty category; (8) Abnormalities of the digestive structure of 60.11% with moderate difficulty category. Analysis of students' learning difficulties showed 6 factors causing learning difficulties which consisted of (1) too much Latin as much as 88.01%; (2) Difficulty understanding the material as much as 81.09%; (3) The teacher's explanation is not understood by 67.60%; Lack of books from other sources as much as 61.42%; (5) Lack of learning media as much as 60.11%; and (6) The material seems too abstract as much as 53.75%.